GAMBARAN MANAJEMEN PENGELOLAAN LIMBAH MEDIS PADAT DI PUSKESMAS KEDIRI KABUPATEN LOMBOK BARAT TAHUN 2024 - Yasinda Yasinda; Abdul Aziz Fatryawan; Januari Lesmana; I M Putu Sudiartha H (Nusadaya Journal of Multidiciplinary Studies, 2024)
Medical waste is infectious waste, radiological waste, cytotoxic waste and laboratory waste. Puskesmas is a health service unit that produces medical and non-medical waste, both solid and liquid, in its activities. Waste and rubbish that is not managed properly can be a factor causing environmental problems. Garbage and waste is a serious problem and cannot be considered trivial, which occurs in various countries, especially in Indonesia. This research aims to find out an overview of solid medical waste management at the Kediri Community Health Center, West Lombok Regency. This research is a descriptive study using observations in the form of a checklist of RI Minister of Health No. 18 of 2020. The management of solid medical waste at the Kediri Public Health Center, West Lombok district has met the requirements according to Minister of Health Regulation No. 18 of 2020 concerning Medical Waste Management for Regional-Based Health Service Facilities related to the process of sorting and containing, transporting, collecting and destroying.